Kepraktisan Penggunaan Laboraturium Virtual Dengan Pendekatan STEM (Science, Technology, Engineering And Mathematics) Di Sekolah Dasar - Dewi, Mera Putri; Fitria, Yanti (Universitas PGRI Madiun, 2023)
The purpose of this study is to describe the practicality of developing virtual laboratories in thematic learning with the STEM approach in elementary schools. The research conducted is development research. The development model used is 4D (define, design, develop, and disseminate. This data collection technique uses practicality test questionnaires by educators and uses student response questionnaires in individual, small group, and limited group trials. The data in this practical instrument is then analyzed quantitatively by carrying out calculations using the practicality formula.Based on the results of the practicality test the virtual laboratory that was developed was included in the very practical category with the percentage of practicality tests obtained by educators obtaining an average total score of 87.64%.Group trials conducted on three people students obtained an average total score of 89.89%, small group trials consisting of 6 students obtained an average total score of 84.10%. Furthermore, limited group trials were conducted on 20 students obtaining an average total score of 91.94% It can betconcludedtthat the virtual laboratory d developed already meet the very practical criteria